P191 Development and validation of a 13-item short version of the IBD self-efficacy scale. (21st January 2022) - Tanaka, M; Kawakami, A; Sakagami, K; Terai, T; Fernandez, J; Keefer, L; Ito, H
Abstract: Background: The IBD-Self-Efficacy Scale (IBD-SES) is an outcome measurement scale used in various countries, with psychometric properties that predicted psychological distress and showed moderate correlation with QOL. Although the 29-item IBD-SES is useful, a shorter instrument would increase the likelihood of usage. In this study, we aimed to develop a substantially shorter, but still as valid version of IBD-SES. Methods: A total of 919 patients, 482 from a specialized IBD clinic (UC: 184, CD: 298) and 437 online (UC: 255, CD: 182), were used for psychometric assessment. The original 29-item IBD-SES was reduced using three major analytic steps (assessed ceiling or floor effect, correlation between items, test-retest reliability). The shorter version was evaluated on construct validity by confirmatory factor analysis, criterion validity by Pearson's correlation coefficients with original version, and internal consistency by Cronbach's alpha coefficient. Results: In the item reduction process, the following items were removed: 2 items due to a ceiling effect, 12 additional items due to high correlation, 2 more items due to a low intraclass correlation coefficient (ICC). The short version was confirmed to consist of the same 4 subscales as the original version, [Managing Stress and Emotions], [Managing Medical Care], [Managing Symptoms and Disease] and [Maintaining Remission] and was validated by confirmatory factor analysis. The fit indices were as follows: Normed χ2 = 7.18 (p < 0.001), comparative fit index (CFI) = 0.94, goodness-of-fit index (GFI) = 0.93, adjusted goodness-of-fit index (AGFI) =0.89, parsimony goodness-of-fit index (PGFI) = 0.60, and the root mean square error of approximation (RMSEA) = 0.084. Correlation with the original IBD-SES in each subscale was high (0.97–0.98). Cronbach's alpha for each subscale ranged from 0.68 to 0.86. Conclusion: The study showed that the revised scale has improved psychometric properties and demonstrated the reliability and validity of the IBD-SES13. The revised scale could provide clinical usefulness with the possibility of higher response rates.